Non-Invasive in Vivo Quantification of Directional Dependent Variation in Mechanical Properties for Human Skin - Lakhani, Piyush; Dwivedi, Krashn K.; Parashar, Atul; Kumar, Navin (Frontiers in Bioengineering and Biotechnology, 2021)
Skin is the body's largest organ, and it shows non-linear and anisotropic behavior under the deformation. This behavior of the skin is due to the waviness and preferred orientation (in a particular direction) of collagen fibers. This preferred orientation of collagen fibers results in natural pre-tension and anisotropy of the skin. The knowledge of natural skin pre-tension and anisotropy is essential during incisions and surgery. The available suction-based devices quantify the anisotropy through the displacement field and cannot measure the stress-strain relation in particular directions. Therefore, in the current study, an in vivo full-field measurement suction apparatus was developed to measure the stress and strain of skin in all planar directions through a single experiment. First, this apparatus was tested on silicone substrates of known properties, and then it was used to test the skin of twelve human forearms. Further, to check the effect of hand stability on the measurements, the obtained results of the skin were compared with the results of a standard test performed in the same skin using a steady setup. The consistency between these two results confirms that the stability of the hand does not influence the measurements of skin properties. Furthermore, using the developed apparatus, the skin's anisotropy and its relation with the Kraissl's lines orientation was quantified by measuring the toe and linear moduli at an interval of one degree. The minimum and maximum values of the toe and linear moduli were 0.52 ± 0.09 and 0.59 ± 0.11 MPa, and 3.09 ± 0.47 and 5.52 ± 1.13 MPa, respectively. Also, the direction of maximum moduli was found almost similar to Kraissl's lines' orientation. These results confirm the contribution of skin pre-tension on the anisotropy of the skin. The present apparatus mimics the tissue expansion procedure, where observation of the test may be helpful in the selection of size and shape of the expander.